2009
DOI: 10.1099/jmm.0.004770-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the anaerobic intestinal spirochaete Brachyspira pilosicoli from long-term residents and Indonesian visitors to Perth, Western Australia

Abstract: Brachyspira pilosicoli is an anaerobic spirochaete that colonizes the large intestine of humans and various species of animals and birds. The spirochaete is an important enteric pathogen of pigs and poultry, but its pathogenic potential in humans is less clear. In the current study, the occurrence of B. pilosicoli in faecal samples from 766 individuals in two different population groups in Perth, Western Australia, was investigated by selective anaerobic culture. Of 586 individuals who were long-term residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In a study of healthy immigrants to Western Australia, carriage was detected in 10.6% of the population, with the prevalence being significantly higher among individuals from the Middle East and from Africa than among individuals from other regions (170). In another study, a fecal carriage rate of 15% was found among 227 recent healthy immigrants to Australia (169).…”
Section: Immigrants and Visitors To Developed Countriesmentioning
confidence: 95%
See 3 more Smart Citations
“…In a study of healthy immigrants to Western Australia, carriage was detected in 10.6% of the population, with the prevalence being significantly higher among individuals from the Middle East and from Africa than among individuals from other regions (170). In another study, a fecal carriage rate of 15% was found among 227 recent healthy immigrants to Australia (169).…”
Section: Immigrants and Visitors To Developed Countriesmentioning
confidence: 95%
“…In another study, a fecal carriage rate of 15% was found among 227 recent healthy immigrants to Australia (169). In the original study, feces from 17 of 180 (9.4%) Indonesians who either were short-term or medium-term visitors to Perth, Western Australia, were found to be culture positive for B. pilosicoli (170). The colonized individuals had lived in Perth for periods varying from 10 days to 4.5 years (with a median duration of 5 months).…”
Section: Immigrants and Visitors To Developed Countriesmentioning
confidence: 99%
See 2 more Smart Citations
“…A review collating global human clinical manifestations and prevalence of B. pilosicoli [2] cites that it is commonly found in faecal samples collected in the Middle East, Southeast Asia and rural Australia, but for example is less prevalent (~1.5 %) in urban parts of Australia [32], the UK and Belgium.…”
Section: Introductionmentioning
confidence: 99%